Safety and Efficacy of Pneumatic Lithotripters Versus Holmium Laser in Management of Ureteral Calculi: A Randomized Clinical Trial - Razzaghi, Mohammad Reza; Razi, Abdollah; Mazloomfard, Mohammad Mohsen; Golmohammadi Taklimi, Amin; Valipour, Reza; Razzaghi, Zahra (Urology Journal, 2013)
PURPOSE: To compare efficacy and safety of holmium:YAG laser and pneumatic lithotripter in the management of ureteral stones. MATERIALS AND METHODS: One hundred and twelve patients with 1 to 2 cm ureteral calculi were selected for pneumatic or holmium:YAG laser transurethral ureterolithotripsy (56 patients in each group). Ultrasonography and plain abdominal x-ray were performed for all the patients before the operation. The pneumatic lithoclast was Swiss LithoClast, while in laser lithotripsy, holmium:YAG laser frequency was used, which was usually set between 5 and 10 Hz at a power of 10 to 15 Watt. Intravenous urography was performed for all the patients at 3 months to assess functional status and to delineate the ureteral anatomy. RESULTS: The mean patients’ age and stones’ size were the same in both groups, and there were no statistical differences. Mean duration of lithotripsy was 13.7 ± 12.6 minutes in laser group and 7.9 ± 4.2 minutes in pneumatic lithotripsy group. Immediate stone-free rate was 100% and 82.1% in the laser and pneumatic groups, respectively (P = .001). Stone pushing back occurred only in 10 (17.9%) patients in pneumatic group. In terms of complications, such as perforation, mucosal injury, and bleeding, there were no differences between the two groups. No intravenous pyelography related complication was seen at 3-month follow-up. CONCLUSION: Laser lithotripsy is a superior approach for the management of upper ureteral stones of 1 to 2 cm in size due to its higher rate of stone clearance.